A hard carbon / soft carbon / graphite ternary composite carbon material and its preparation method and application

By using one-step carbonization method to prepare hard carbon/soft carbon/graphite ternary composite carbon materials in potassium ion batteries, the problems of low specific capacity and poor cycle stability of graphite negative electrodes in potassium ion batteries are solved, and the effect of improving potassium ion transfer speed and cycle stability is achieved.

CN115863566BActive Publication Date: 2025-03-18GUANGDONG UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211470551.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-23
Publication Date
2025-03-18
Estimated Expiration
2042-11-23

AI Technical Summary

Technical Problem

The problem of low specific capacity of graphite negative electrode in potassium ion batteries and poor circulation stability.

Method used

Hard carbon/soft carbon/graphite ternary composite carbon material is prepared by mixing graphite, soft carbon precursor and hard carbon precursor powder in a specific proportion and calcining in an inert gas atmosphere. The hard carbon cladding layer of this material has a large layer spacing, and the soft carbon cladding layer has a short-range ordered graphite structure and rich defect adsorption sites, which can buffer the volume changes of potassium ions and improve its transmission speed.

Benefits of technology

It improves the transfer speed and cycle stability of potassium ions, increases the reversible potassium storage capacity, and is suitable for negative electrode materials for potassium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003958370770000071
    Figure BDA0003958370770000071
  • Figure BDA0003958370770000081
    Figure BDA0003958370770000081
  • Figure HDA0003958370780000011
    Figure HDA0003958370780000011
Patent Text Reader

Abstract

The present invention discloses a hard carbon / soft carbon / graphite ternary composite carbon material and a preparation method and application thereof. The present invention uses graphite and soft carbon precursors such as polyvinyl chloride, asphalt, petroleum coke, and hard carbon precursor powders such as lignin, glucose, starch, etc. as raw materials, and adopts a one-step carbonization method to prepare a hard carbon / soft carbon / graphite ternary composite carbon material. Compared with traditional graphite negative electrode materials for potassium ion batteries, the present method can obtain a hard carbon / soft carbon / graphite ternary composite carbon negative electrode material without further purification, which can not only improve the transmission speed of potassium ions, but also buffer the volume change caused by the insertion / extraction process of potassium ions, thereby improving its cycle stability; the use of hard carbon coating can reduce the graphitization structure of soft carbon, shorten the length of graphene sheets, and increase the diffusion rate of K ions in soft carbon; the constructed hard carbon / soft carbon / graphite ternary composite carbon negative electrode material improves its reversible capacity and cycle stability of potassium storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrochemical technology, and in particular relates to a hard carbon / soft carbon / graphite ternary composite carbon material and a preparation method thereof and application in potassium ion batteries. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, good cycle stability and long life, and are widely used in portable electronic products and electric vehicles. However, lithium resources are relatively scarce, making it difficult to meet the growing demand for large-scale renewable energy generation and energy storage. Therefore, there is an urgent need to research and develop cost-effective secondary battery systems. Potassium-ion batteries have the following advantages: (1) high abundance of potassium resources; (2) potassium-ion batteries have a rocking chair working mechanism similar to that of lithium-ion batteries; (3) potassium ions can be reversibly embedded / extracted in graphite; (4) the potassium metal negative electrode has a redox potential (K) close to that of lithium metal. + / K's -2.93V vs Li + These advantages make potassium-ion batteries a potential choice in the post-lithium-ion battery era.

[0003] Although potassium ion batteries have the potential to replace lithium ion batteries, it is extremely challenging to find anode materials suitable for potassium ion batteries. Potassium ions have a large ionic radius (K + The radius is Li + The radius is ), it is relatively difficult to embed and diffuse in alloy-type and conversion-type negative electrode materials, and the volume expansion is large. Therefore, the potassium embedding process destroys the material structure and reduces the cycle stability of potassium ion storage. Carbon materials are widely used due to their high conductivity, low operating voltage, and good structural adjustability. At present, graphite is a widely used negative electrode material in commercial lithium batteries. The article (J.Am.Chem.Soc.2015,137,36,11566–11569) reported for the first time the phenomenon of electrochemical reversible embedding of potassium ions into graphite in non-aqueous electrolytes, with a capacity of up to 279 mAh / g, but K + Intercalation in graphite can cause up to 60% volume expansion, resulting in poor cycle stability. After 50 cycles at a current density of C / 2 (C=279mA / g), the capacity retention rate of graphite is only 50%, so it is difficult to use it as a practical negative electrode material. In addition to graphite negative electrodes, amorphous carbon materials (hard carbon and soft carbon) can also be used as potassium storage negative electrode materials for potassium ion batteries. Hard carbon materials are usually obtained by carbonization of oxygen-containing polymers such as resins and biomass. They have the characteristics of large interlayer spacing and can buffer the volume expansion of the carbon layer caused by potassium ion insertion. However, their highly disordered structure will cause K +Problems such as large ion transport resistance and slow reaction kinetics lead to poor rate performance of hard carbon (Advanced Energy Materials, 2016, 6, 1501874). However, compared with hard carbon, soft carbon has a large number of short-range ordered graphite-like structures, which will be conducive to the rapid transport of potassium ions, accelerate the reaction kinetics of potassium insertion / extraction, and help improve its rate performance (Advanced Materials, 2020, 32, 2000505). The article (Advanced Functional Materials, 2017, 27, 1700324) synthesized a soft carbon derived from the organic compound perylenetetracarboxylic dianhydride (PTCDA), with a capacity of 264 mAh / g at a current density of C / 10 (C = 279 mAh / g), and its capacity retention rate was only 55% after 200 cycles at a current density of 1C. The soft carbon has poor cyclic stability and is therefore not suitable for practical applications. Summary of the invention

[0004] In view of the problems of low specific capacity and poor cycle stability of graphite negative electrode in potassium ion batteries, the primary purpose of the present invention is to provide a method for preparing a hard carbon / soft carbon / graphite ternary composite carbon material.

[0005] The present invention adopts graphite and soft carbon precursors such as polyvinyl chloride, asphalt, petroleum coke, and hard carbon precursors such as lignin, glucose, starch, etc., and adopts a one-step carbonization method to prepare a hard carbon / soft carbon / graphite ternary composite carbon material. The hard carbon coating layer of the composite carbon material has a large interlayer spacing, and its soft carbon coating layer has a short-range ordered graphite-like structure and abundant defect adsorption sites, which can not only improve the transmission speed of potassium ions, buffer the volume change caused by potassium ions in the process of embedding / de-embedding, improve its cycle stability, but also provide a higher reversible potassium storage capacity.

[0006] Another object of the present invention is to provide a hard carbon / soft carbon / graphite ternary composite carbon material obtained by the above preparation method.

[0007] Another object of the present invention is to provide an application of the above-mentioned hard carbon / soft carbon / graphite ternary composite carbon material in the negative electrode of a potassium ion battery.

[0008] The purpose of the present invention is achieved through the following technical solutions:

[0009] A method for preparing a hard carbon / soft carbon / graphite ternary composite carbon material comprises the following steps:

[0010] Graphite, soft carbon precursor and hard carbon precursor powders are uniformly mixed in a mass ratio of 100:3-36:3-36, and calcined at 500-1700° C. for 0.5-10 hours in an inert gas atmosphere to obtain a hard carbon / soft carbon / graphite ternary composite carbon material.

[0011] Preferably, the soft carbon precursor is at least one of polyvinyl chloride, asphalt and petroleum coke.

[0012] Preferably, the hard carbon precursor is at least one of lignin, glucose and starch.

[0013] Preferably, the uniform mixing refers to first mechanical mixing and then grinding mixing, and the grinding time is 10 to 200 minutes.

[0014] Preferably, the inert gas is at least one of a rare gas and nitrogen.

[0015] Preferably, the heating rate of the calcination is 1 to 30° C. / min, and the inert gas flow rate is 2 to 100 mL / min.

[0016] Preferably, the calcination time is 2 to 10 hours.

[0017] Preferably, the method for preparing the hard carbon / soft carbon / graphite ternary composite carbon material comprises the following steps:

[0018] Graphite, polyvinyl chloride, asphalt, petroleum coke, lignin, glucose and starch are uniformly mixed in a mass ratio of 100:1-12:1-12:1-12:1-12:1-12:1-12, and calcined at 500-1700°C for 0.5-10h in an inert gas atmosphere to obtain a hard carbon / soft carbon / graphite ternary composite carbon material.

[0019] The preparation method mentioned above obtains a hard carbon / soft carbon / graphite ternary composite carbon material.

[0020] The application of the above-mentioned hard carbon / soft carbon / graphite ternary composite carbon material in the negative electrode of potassium ion battery.

[0021] In the present invention, soft carbon such as asphalt, polyvinyl chloride and petroleum coke can be used to coat powdered graphite to buffer the expansion of graphite carbon layer and improve the cycle stability of potassium ion battery. 3 Carbon can connect sp of polyvinyl chloride, graphite, asphalt, petroleum coke, etc. 2 carbon layer, increasing the interlayer spacing, and sp 3 The formation of carbon can reduce the crystallinity of carbon materials and reduce the sp 2 The degree of carbon cross-linking makes the carbon layer more short-range ordered, thus improving the rate capability of potassium ion batteries.

[0022] The present invention constructs a hard carbon / soft carbon / graphite composite structure, which can not only increase the transmission speed of potassium ions, but also buffer the volume change caused by potassium in the embedding / extraction process, thereby improving its cycle stability. Soft carbon is easily graphitized during the carbonization process, so hard carbon coating can be used to reduce the graphitized structure of soft carbon, shorten the length of graphene sheets, and increase the transmission speed of K ions in soft carbon. Constructing a hard carbon / soft carbon / graphite ternary composite carbon negative electrode material can improve its reversible capacity and cycle stability.

[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0024] (1) Precursors such as graphite, polyvinyl chloride, asphalt, petroleum coke, lignin, glucose, and starch are abundant in source and extremely low in cost, making them suitable for the development of commercial negative electrode materials.

[0025] (2) The hard carbon / soft carbon coating has short-range ordered graphite-like layers with large interlayer spacing and abundant defect adsorption sites, which can alleviate volume expansion, improve the kinetics of potassium ion insertion and extraction, and increase the reversible capacity.

[0026] (3) The one-step carbonization method is adopted, no post-processing is required, the overall process is simple, and it is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a SEM image of the hard carbon / soft carbon / graphite ternary composite carbon material prepared by the preparation method of Example 1.

[0028] Figure 2 : This is the XRD diagram of the hard carbon / soft carbon / graphite ternary composite carbon material prepared by the preparation method of Example 1. DETAILED DESCRIPTION

[0029] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.

[0030] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.

[0031] Example 1

[0032] (1) Take graphite, polyvinyl chloride, asphalt, petroleum coke, lignin, glucose, and starch powder in a mass ratio of 100:4:3:6:3:2:1, grind them in a mortar for 20 min, and then place them in a corundum boat.

[0033] (2) The corundum boat was placed in an inert gas protected tubular furnace for calcination at a heating rate of 5°C / min to 1000°C and carbonized for 2 h.

[0034] Example 2

[0035] (1) Take graphite, polyvinyl chloride, asphalt, petroleum coke, lignin, glucose, and starch powder in a mass ratio of 100:9:10:12:3:2:1, grind them in a mortar for 20 min, and then place them in a corundum boat.

[0036] (2) The corundum boat was placed in an inert gas protected tubular furnace for calcination at a heating rate of 5°C / min to 1100°C and carbonized for 2 h.

[0037] Example 3

[0038] (1) Take graphite, polyvinyl chloride, asphalt, petroleum coke, lignin, glucose, and starch powder in a mass ratio of 100:4:3:6:3:5:4, grind them in a mortar for 20 min, and then place them in a corundum boat.

[0039] (2) The corundum boat was placed in an inert gas protected tubular furnace for calcination at a heating rate of 5°C / min to 1200°C and carbonized for 2h.

[0040] Example 4

[0041] (1) Take graphite, polyvinyl chloride, asphalt, petroleum coke, lignin, glucose, and starch powder in a mass ratio of 100:9:10:12:3:5:4, grind them in a mortar for 20 min, and then place them in a corundum boat.

[0042] (2) The corundum boat was placed in an inert gas protected tubular furnace for calcination at a heating rate of 5°C / min to 1300°C and carbonized for 2h.

[0043] Example 5

[0044] (1) Take graphite, polyvinyl chloride, asphalt, petroleum coke, lignin, glucose, and starch powder in a mass ratio of 100:4:3:6:8:12:10, grind them in a mortar for 20 min, and then place them in a corundum boat.

[0045] (2) The corundum boat was placed in an inert gas protected tubular furnace for calcination at a heating rate of 5°C / min to 1500°C and carbonized for 2 h.

[0046] Example 6

[0047] (1) Take graphite, polyvinyl chloride, asphalt, petroleum coke, lignin, glucose, and starch powder in a mass ratio of 100:4:3:6:3:2:1, grind them in a mortar for 20 min, and then place them in a corundum boat.

[0048] (2) The corundum boat was placed in an inert gas protected tubular furnace for calcination at a heating rate of 5°C / min to 1700°C and carbonized for 2 h.

[0049] Example 7

[0050] (1) Take graphite, polyvinyl chloride, asphalt, petroleum coke, lignin, glucose, and starch powder in a mass ratio of 100:9:10:12:3:2:1, grind them in a mortar for 20 min, and then place them in a corundum boat.

[0051] (2) The corundum boat was placed in an inert gas protected tubular furnace for calcination at a heating rate of 5°C / min to 900°C and carbonized for 2h.

[0052] Example 8

[0053] (1) Take graphite, polyvinyl chloride, asphalt, petroleum coke, lignin, glucose, and starch powder in a mass ratio of 100:4:3:6:3:5:4, grind them in a mortar for 20 min, and then place them in a corundum boat.

[0054] (2) The corundum boat was placed in an inert gas protected tubular furnace for calcination at a heating rate of 5°C / min to 800°C and carbonized for 2h.

[0055] Example 9

[0056] (1) Take graphite, polyvinyl chloride, asphalt, petroleum coke, lignin, glucose, and starch powder in a mass ratio of 100:9:10:12:3:5:4, grind them in a mortar for 20 min, and then place them in a corundum boat.

[0057] (2) The corundum boat was placed in an inert gas protected tubular furnace for calcination at a heating rate of 5°C / min to 700°C and carbonized for 2 h.

[0058] Example 10

[0059] (1) Take graphite, polyvinyl chloride, asphalt, petroleum coke, lignin, glucose, and starch powder in a mass ratio of 100:4:3:6:8:12:10, grind them in a mortar for 20 min, and then place them in a corundum boat.

[0060] (2) The corundum boat was placed in an inert gas protected tubular furnace for calcination at a heating rate of 5°C / min to 600°C and carbonized for 2h.

[0061] Comparative Example 1

[0062] (1) Take 5 g of graphite powder, grind it in a mortar for 20 min, and then place it in a corundum boat.

[0063] (2) The corundum boat was placed in an inert gas protected tubular furnace for calcination at a heating rate of 5°C / min to 1000°C and carbonized for 2 h.

[0064] Comparative Example 2

[0065] (1) Take graphite, polyvinyl chloride, asphalt, and petroleum coke powders in a mass ratio of 100:4:3:6, grind them in a mortar for 20 min, and then place them in a corundum boat.

[0066] (2) The corundum boat was placed in an inert gas protected tubular furnace for calcination at a heating rate of 5°C / min to 1000°C and carbonized for 2 h.

[0067] Comparative Example 3

[0068] (1) Take graphite, lignin, glucose, and starch powders in a mass ratio of 100:3:2:1, grind them in a mortar for 20 min, and then place them in a corundum boat.

[0069] (2) The corundum boat was placed in an inert gas protected tubular furnace for calcination at a heating rate of 5°C / min to 1000°C and carbonized for 2 h.

[0070] The specific preparation method of the negative electrode material and the potassium ion battery comprises the following steps:

[0071] The hard carbon / soft carbon / graphite ternary composite carbon material obtained by the above method was placed in a vacuum drying oven at 80°C and dried for 12 hours. Grind evenly according to the negative electrode material: conductive carbon black: carboxymethyl cellulose = 8:1:1 (mass ratio), apply it on the copper foil, and place the coated electrode in an 80°C blast oven for 12 hours, and then place it in a vacuum drying oven at 80°C for 8 hours. The battery was assembled in an argon-protected glove box. The electrolyte was 0.8 mol / L KPF6 in ethylene carbonate and diethyl carbonate solution (EC:DEC = 1:1 (volume ratio), and the metal potassium sheet was the counter electrode.

[0072] The SEM image of the hard carbon / soft carbon / graphite ternary composite carbon material obtained by the above method is as follows: Figure 1 As shown, it presents an irregular granular structure. The XRD pattern of the hard carbon / soft carbon / graphite ternary composite carbon material obtained by the above method is as follows Figure 2 As shown, only the diffraction peaks of amorphous carbon appear at 26° and 42°, indicating that the graphite has been coated with soft carbon and hard carbon coating layers.

[0073] Table 1 Reversible specific capacity and capacity retention rate of different carbon materials

[0074]

[0075]

[0076] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a hard carbon / soft carbon / graphite ternary composite carbon negative electrode material for a potassium ion battery, characterized in that: The following steps are involved: Graphite, soft carbon precursor and hard carbon precursor powders are mixed uniformly in a mass ratio of 100:3-36:3-36, and calcined at 500-1700°C for 0.5-10 h in an inert gas atmosphere to obtain a hard carbon / soft carbon / graphite ternary composite carbon negative electrode material; The soft carbon precursor is at least one of polyvinyl chloride, asphalt and petroleum coke; The hard carbon precursor is at least one of lignin, glucose and starch; The heating rate of the calcination is 1-30°C / min, and the flow rate of the inert gas is 2-100 mL / min.

2. The method for preparing a hard carbon / soft carbon / graphite ternary composite carbon negative electrode material for a potassium ion battery according to claim 1, characterized in that: The calcination temperature is 600-1700°C.

3. The method for preparing a hard carbon / soft carbon / graphite ternary composite carbon negative electrode material for a potassium ion battery according to claim 1, characterized in that: The calcination time is 2 h.

4. The method for preparing a hard carbon / soft carbon / graphite ternary composite carbon negative electrode material for a potassium ion battery according to claim 1, characterized in that: The uniform mixing means first mechanical mixing and then grinding mixing, and the grinding time is 10 to 200 minutes.

5. The method for preparing a hard carbon / soft carbon / graphite ternary composite carbon negative electrode material for a potassium ion battery according to claim 1, characterized in that: The calcination time is 2 to 10 h.

6. The method for preparing a hard carbon / soft carbon / graphite ternary composite carbon negative electrode material for a potassium ion battery according to claim 1, characterized in that: The inert gas is at least one of a rare gas and nitrogen.

7. The method for preparing a hard carbon / soft carbon / graphite ternary composite carbon negative electrode material for a potassium ion battery according to claim 1, characterized in that: The method for preparing the hard carbon / soft carbon / graphite ternary composite carbon negative electrode material for potassium ion batteries comprises the following steps: Graphite, polyvinyl chloride, asphalt, petroleum coke, lignin, glucose and starch are uniformly mixed in a mass ratio of 100:1-12:1-12:1-12:1-12:1-12:1-12, and calcined at 500-1700°C for 0.5-10 h in an inert gas atmosphere to obtain a hard carbon / soft carbon / graphite ternary composite carbon negative electrode material.

8. A hard carbon / soft carbon / graphite ternary composite carbon negative electrode material for potassium ion batteries prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the hard carbon / soft carbon / graphite ternary composite carbon negative electrode material for potassium ion batteries as described in claim 8 in the negative electrode of potassium ion batteries.

Citation Information

Patent Citations

  • Power lithium-ion battery negative electrode material with core-shell structure and preparation method thereof

    CN103811717A